A SURVEY STUDY OF HUMAN CAPITAL AND EDUCATIONAL ATTAINMENT - Rininta Nurrachmi (Airlangga International Journal of Islamic Economics and Finance, 2019)
The development of human capital is the essential thing to determine a country’s growth. The existence of a country’s human capital quality depends on its education. The change of information in society is going rapidly and it is important to cope up with information and knowledge to all economic process. With the role of human capital in the modern societies many people are still unaware about the process of educational production. This paper is aimed to provide the process on human capital formation and educational attainment from microeconomic perspective. The literature reviews indicate that education attainment in the society are influence by many factors namely religion, family background, teacher’s quality and incentive, and the peer effects. In the empirical studies, Mincerian wage equation is the most widely used to analyze education and earnings. Besides from educational production function, to determine the quality of human capital, fiscal policy through taxation and educational subsidies have impact to the end result of students.